Popreligia w szlafroku. Dudeizm jako zjawisko kulturowe (Przegląd Religioznawczy – The Religious Studies Review, 2020)
This paper deals with the cultural roots of the phenomena of dudeism. Dudeism is a new religious movement that emerged in the context of popular culture, especially the cinematic experience offered by teh 1998 movie Big Lebowski directed by the Coen brothers. The dudeist philosophy is hoewever not only rooted in the motives found in the mentioned picture, but also in selected eastern religions and philosophies, among which Taoism is the most significant. This marriage of traditional religiosity and new pop-cultural ideas makes the success of Dudeism in a long run. This movement can however be considered also nit just as a strictly religious phenomena, but a cultural one as well. Dudeism considered as a subculture might be interpreted in three major perspectives, evolutionary, the cultural industry and subversive. All three methodological approaches are bieng considered in this paper as important not only in understanding the phenomena of dudeism itself, but also the nature of modern religious dynamics.